2009
DOI: 10.4040/jkan.2009.39.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Public Health Center Smoking Cessation Counseling Program using the Transtheoretical Model

Abstract: Purpose:The purpose of this study was to identify the effectiveness of public health center smoking cessation counseling program using the transtheoretical model on the process of change, smoking temptation, decisional balance and stage change transition. Methods: A nonequivalent control group non-synchronized design was used for this study. The study population was 115 adult smokers. The counseling program was administered to the experimental group and a smoking cessation program from the Korean Ministry of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
2
5
1
1
Order By: Relevance
“…Literature reviews revealed that the behavioral stages of change model [12][13][14][15] have been applied to smoking cessation both within the country and abroad. Smokers were classified in the individual preparedness and need assessments following the stages of change [16].…”
Section: Introductionmentioning
confidence: 99%
“…Literature reviews revealed that the behavioral stages of change model [12][13][14][15] have been applied to smoking cessation both within the country and abroad. Smokers were classified in the individual preparedness and need assessments following the stages of change [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, smokers in the preparatory stage of a behavioral change do not easily show a behavioral change despite having a greater level of intention that that of smokers in the contemplation stage [ 19 ]. Therefore, the main factors affecting the intention to quit smoking need to be determined for smokers with little or no intention to quit.…”
Section: Introductionmentioning
confidence: 99%
“…These studies described general, smoking-related and health-related characteristics of smokers during different behavioral change stages [ 21 ]. Few studies have reported on factors that influence the intention to quit smoking or whether the attempts were successful [ 18 , 19 , 22 ]. In these studies, the subjects were small groups of young adults, office workers and participants in various healthcare center smoking cessation programs.…”
Section: Introductionmentioning
confidence: 99%
“…Since, this theoretical model can be adopted for tailored education for behavioral change [1314], it has been applied to manage and change behaviors related to physical activity intervention [151617], smoking cessation [1819], drinking cessation [20], and game addiction intervention [21] for adolescents, adults, and older adults; however, it has not been as extensively applied in respect of children. A recent systematic review [22] has shown that there have been 28 intervention studies directed at eating behaviors using the TTM that reported positive results for reduction of fat intake, an increase in the intake of fruits and vegetables, and increases in physical activity.…”
Section: Introductionmentioning
confidence: 99%